2020
DOI: 10.19126/suje.626156
|View full text |Cite
|
Sign up to set email alerts
|

Language Assessment Literacy Level of EFL Teachers: A Focus on Writing and Speaking Assessment Knowledge of the Teachers

Abstract: This study aims to explore Language Assessment Knowledge (LAK) level of high school EFL teachers in terms of assessment of writing and speaking. In addition, another purpose of this study is to investigate whether there is any significant effect of some demographic variables (years of teaching experience, type of undergraduate degree, attending a training course) on teachers' assessment of writing and speaking knowledge. The previous studies focus on university or primary school context in Turkey; however, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…These results are in line with Ölmezer-Öztürk and Aydın (2019). Similarly, Genç et al (2020) investigated the LAK level of high school EFL teachers in assessing writing and speaking and found that teachers were knowledgeable in assessing speaking, whereas their knowledge in assessing writing was significantly low. Thus, it can be interpreted that the EFL teachers in the primary, middle, and high schools in Türkiye are more knowledgeable in reading and speaking assessment, while their knowledge is in writing and listening assessment even though they demonstrated a higher degree of LAK in general.…”
Section: Discussion Conclusion Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in line with Ölmezer-Öztürk and Aydın (2019). Similarly, Genç et al (2020) investigated the LAK level of high school EFL teachers in assessing writing and speaking and found that teachers were knowledgeable in assessing speaking, whereas their knowledge in assessing writing was significantly low. Thus, it can be interpreted that the EFL teachers in the primary, middle, and high schools in Türkiye are more knowledgeable in reading and speaking assessment, while their knowledge is in writing and listening assessment even though they demonstrated a higher degree of LAK in general.…”
Section: Discussion Conclusion Recommendationsmentioning
confidence: 99%
“…It is also seen that research on LAL in Türkiye has lately become a subject of interest since most of the studies have been conducted in recent years. In the studies, knowledge (Genç et al, 2020;Ölmezer-Öztürk & Aydın, 2019), perceptions and practices (Arslan & Üçok-Atasoy, 2020;Büyükkarcı, 2014;Işık, 2021;Kırkgöz et al, 2017;Önalan & Gürsoy, 2020;Öz & Atay, 2017;Tanyer & Susoy, 2018), training needs (Ballıdağ & İnan-Karagül, 2021;Mede & Atay, 2017), and problems (Büyükkarcı, 2014;Tuzcu-Eken, 2016) as well as the impact of demographic and contextual factors (Büyükkarcı, 2016;İnan-Karagül et al, 2017) on language assessment have been analyzed. Higher educational context was mainly preferred by the researchers in Türkiye whereas the research regarding K-12 context is limited.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an internal reason for the growing popularity of language assessments in English language teaching, which has to do with teachers' understanding of the importance of assessment in the language learning process. (Genc et al, 2020) In Assessing Speaking, the personality of the test taker (teacher) has a significant effect on the examinee, the result of the test and the flow of the task. Sullivan (2000) classifies a number of qualities in the examiners.…”
Section: B Teachers Role In Assessing Speakingmentioning
confidence: 99%
“…Hence it is essential to understand how language teachers respond to this new demand and how they possess the competencies expected to face this challenge. In addition to that, most studies reported low to moderate levels of teachers' assessment literacy (Kılıç, 2022;Massey et al, 2020;Genç, et al, 2020;Umam & Indah, 2020;Al-bahlani, 2019), the underdeveloped teachers' assessment literacy to lack of pre-service language assessment training (Bustamante, 2022;Puspawati, 2022;DeLuca & Johnson, 2017;Lam, 2015), and weak assessment knowledge results to the measures used in assessment literacy studies (Gotch & French, 2014). These aforementioned studies mostly used a survey to assess competence, practices, and knowledge.…”
Section: Introductionmentioning
confidence: 99%